A novel method for the on-line analysis of fermentation broth using a sampling device, microcentrifuge and HPLC - Turner,C; Thornhill,NF; Fish,NM (Biotechnology Techniques, 1993)
This paper describes a novel system for on-line sampling and analysis of whole broth from a fermenter. The system comprises a steam sterilisable sampling device, high speed microcentrifuge and HPLC. We present results characterising the separation efficiency of the microcentrifuge under different conditions, and illustrate the system with glucose and acetate data from an Escherichia coli fermentation using the system. The on-line measurements have been confirmed by off-line analysis. © 1993 Science & Technology Letters.